ANALISIS KEBIJAKAN INTEGRASI TES KEMAMPUAN AKADEMIK DALAM ASESMEN NASIONAL: PERSPEKTIF SOSIOLOGI KEBIJAKAN DAN EVALUASI PENDIDIKAN - Harjono; Cucu Atikah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Educational policy in Indonesia has undergone another significant shift with the issuance of Minister of Primary and Secondary Education Regulation Number 9 of 2026, which integrates the National Assessment (Asesmen Nasional/AN) with a new instrument, the Academic Ability Test (Tes Kemampuan Akademik/TKA). This article aims to critically examine the policy design, its underlying rationale, and its social implications. The study employs a Critical Policy Analysis (CPA) approach, enriched by Stephen J. Ball’s sociology of policy perspective and the theory of Street-Level Bureaucracy. It highlights the tension between the paradigms of Assessment of Learning (AoL) and Assessment for Learning (AfL) arising from the integration of instruments with differing objectives. Document analysis, including Regulation Number 10 of 2025 on Graduate Competency Standards, reveals a misalignment between the holistic orientation of graduate profiles and the cognitively oriented nature of the TKA. Furthermore, the “voluntary” status of TKA risks becoming nominal when its results are used in high-stakes student selection processes. Infrastructure disparities and implementer discretion at the school level further raise concerns regarding test validity and integrity.This study concludes that, without adequate regulation and mitigation, the policy risks reinforcing test-oriented teaching practices, fostering implicit school ranking, and exacerbating educational inequality. Careful and equitable implementation is therefore essential.